Accounting the theories of writing in the classroom - Omar , Shumaila; Wan Mohamed , Wan Nazihah; Tengku Mohamed Fauzi, Tg Nur Liyana (Journal of Islamic, Social, Economics and Development, 2025)
Theoretical frameworks can be credited for not only the organization of phenomena but also for guiding future research and practice. Frameworks from the 1980’s have explored the technicalities of the English Language, and it was not until the mid-1990 that theories began shedding light on cognitive processes integrated in the act of writing. Hence, the purpose of this research is to assess the practicality of theories of writing in the context of the modern-day classroom. The literature review narrowed down on three commonly occurring theories which are socio cultural theory, social cognitive theory and cognitive theory of writing. Each theory was analysed using a triangulation of criteria laid down by Dudley-Brown (1977) and Dennis and Kintsch (2007). The analysis shows that frequent modification is not an appealing trait for any theory, yet most theories of writing have undergone varying levels of modification. Despite outlining various segments of writing, no theory could hold the title of “completion”. The most complete theory is the social cognitive theory of writing as it proves to be viable for use in the contemporary classroom. However, this niche requires in-depth empirical research on the efficacy of such theories and on the factors inhibiting and elevating their effectiveness.